Planning of Technological Development of New Products and Its Impact on the Economic Performance of the Enterprise - Natalia N. Kulikova; Vitaly M. Smolentsev; Alexey I. Tikhonov; Vasiliy S. Kireev; Varvara A. Dikareva (International Journal of Economics and Financial Issues, 2016)
The market economy is characterized by competition of enterprises, defining the upgrade of production. Improvement of the economic activity of industrial enterprises implies development of new methods, forms and mechanisms of creation and mastering of new competitive products designed to ensure the predominant position of enterprises on domestic and foreign markets. Modern approaches to the creation and development of new competitive products high-tech require a huge amount of costs. But on the other hand it is the development of new products allows companies to survive in the current competitive environment. Planning for new products refers to the section of strategic planning. Therefore, the ability of the company to develop and introduce to the market its new product depends on its financial performance. A necessary step in production planning is the development of new products, representing a diverse set of processes and activities in the process which is carried out inspection and testing of structures and technologies to specified technical requirements, development of new forms of organization of production. During the development of new products are achieved the planned production volumes, scheduled economic indicators and technical and economic parameters of products. The period of development of new products begins with production of a prototype and ends with serial production.